2001
DOI: 10.1086/322960
|View full text |Cite
|
Sign up to set email alerts
|

On the Metallicity of Star‐forming Dwarf Galaxies

Abstract: We construct three extreme different scenarios of the star formation histories applicable to a sample of dwarf galaxies, based either on their present metallicity or their luminosity. The three possible scenarios imply different mechanical energy input rates and these we compare with the theoretical lower limits established for the ejection of processed matter out of dwarf galaxies. The comparison strongly points at the existence of extended gaseous haloes in these galaxies, acting as the barrier that allows g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 28 publications
6
38
0
Order By: Relevance
“…All data used for this study are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/572/A90 large fraction of the Hubble time, perhaps coupled with an initial phase of vigorous star formation, is a seemingly viable way of explaining the cessation of star-formation activity in galaxies and is invoked by several studies as the primary method of building up stellar mass in galaxies (e.g., Legrand et al 2001;Noeske et al 2007a,b;James et al 2008;Rodighiero et al 2011;Gladders et al 2013;Oesch et al 2013). This scenario is not, however, the only method of transforming the gas-rich galaxies observed in the high-redshift universe (e.g., Daddi et al 2010a) into those whose baryonic component is dominated by their stellar matter.…”
Section: Introductionmentioning
confidence: 99%
“…All data used for this study are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/572/A90 large fraction of the Hubble time, perhaps coupled with an initial phase of vigorous star formation, is a seemingly viable way of explaining the cessation of star-formation activity in galaxies and is invoked by several studies as the primary method of building up stellar mass in galaxies (e.g., Legrand et al 2001;Noeske et al 2007a,b;James et al 2008;Rodighiero et al 2011;Gladders et al 2013;Oesch et al 2013). This scenario is not, however, the only method of transforming the gas-rich galaxies observed in the high-redshift universe (e.g., Daddi et al 2010a) into those whose baryonic component is dominated by their stellar matter.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors (De Young & Heckman 1994;D'Ercole & Brighenti 1999;MacLow & Ferrara 1999) believe that the metals are easily channelled along the funnel created by the galactic wind, so they are ejected outside the galaxy more easily than the pristine gas. Other authors (Silich & Tenorio-Tagle 1998;Legrand et al 2001) have suggested that the metal-rich gas is barely lost from the galaxies, since it is trapped by extended halos surrounding the galaxies, although the existence of such halos is still unproved. Rieschick & Hensler (2000) have suggested that ∼25% of the metals can mix rapidly, remaining trapped in the galaxy, whereas the other 75% of metals undergoes a cycle lasting ∼1 Gyr, in which an outflow is created.…”
Section: Introductionmentioning
confidence: 99%
“…Kunth & Sargent (1986) point out the self-enrichment of the H II region used for measuring. However, the time-scale for the SN ejecta to cool down and mix is of the order of several hundred Myr (e.g., Legrand et al, 2001) and, thus, longer than the age of the H II regions. This fact eliminates the possibility of self-contamination.…”
Section: Existence Of a Minimum Metallicity For The Star-forming Gasmentioning
confidence: 99%